2003
DOI: 10.1074/jbc.m310252200
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of Putative Catalytic and Regulatory Residues of Streptomyces chromofuscus Phospholipase D Differentially Modifies Phosphatase and Phosphodiesterase Activities

Abstract: Phospholipase D from Streptomyces chromofuscus (sc-PLD) is a member of the diverse family of metallo-phosphodiesterase/phosphatase enzymes that also includes purple acid phosphatases, protein phosphatases, and nucleotide phosphodiesterases. Whereas iron is an essential cofactor for scPLD activity, Mn 2؉ is also found in the enzyme. A third metal ion, Ca 2؉ , has been shown to enhance scPLD catalytic activity although it is not an essential cofactor. Sequence alignment of scPLD with known phosphodiesterases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Within this structural superfamily it has been argued that the PhoD family has greatest similarity to eukaryotic purple acid phosphatases (PAPs) (9). In PAPs the active site metal pair are a Fe 3+ ion and a divalent ion that can be Fe 2+ , Mn 2+ , or Zn 2+ depending on the enzyme (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Within this structural superfamily it has been argued that the PhoD family has greatest similarity to eukaryotic purple acid phosphatases (PAPs) (9). In PAPs the active site metal pair are a Fe 3+ ion and a divalent ion that can be Fe 2+ , Mn 2+ , or Zn 2+ depending on the enzyme (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…The PAPs hydrolyze a broad range of substrates but it is unknown whether their function is promiscuous -as the general alkaline phosphatases PhoA and PhoX are thought to be, or with specific function, as in the PhoD homologue S. chromofuscus PLD, which is thought to have a dedicated role removing the polar head from phospholipid substrates. On the basis of sequence alignment, PhoD was predicted to bear resemblance the PAPs, 14 and indeed, upon structural solution of PhoD, this was found to be the case.…”
Section: Crystallizationmentioning
confidence: 99%
“…As shown in Table 2 the active center, and the Ca 2þ ion is involved in binding to the substrate. 7) Complete inhibition of swPLD by the Fe 3þ and Mn 2þ ions suggests that the structure of the active center was different from that of scPLD. Enhancement of transphosphatidylation with the Ca 2þ ion was rather higher than the hydrolysis, suggesting that the Ca 2þ ion might be important to the action of the OH À ion and to recognition of alcohol as an acceptor of the phosphatidyl group.…”
Section: Effects Of Metal Ions On the Activities Of Swpldmentioning
confidence: 99%
“…5,6) As to S. chromofuscus PLD, it has been suggested that the enzyme requires Fe 3þ and Mn 2þ ions, in addition to the Ca 2þ ion, for construction of the catalytic site. 7) On one hand, these bacterial secretion types of PLDs might generate organophosphates for phosphate retrieval in media, and PLDs, in some bacteria, are important for their physiology as virulence determinants. 8,9) However, with respect to the enzymatical properties and the physiological function of bacterial PLDs, little is known.…”
mentioning
confidence: 99%